Historical Analysis and Calibration of the Oldest Al-Mujahidin Mosque, Parepare City - Faiz, ABD. Karim; Ahmad, Ahmad (University of Muhammadiyah Sumatera Utara, 2023)
According to Surah Al-Baqarah, facing the qibla is a religious requirement in performing salah (prayer). Therefore, the objective of this research is to understand the methods used to determine the qibla direction of Masjid Al-Mujahidin in Parepare and analyze the calibration of its qibla direction. This research employs a qualitative approach with field research methodology. Data analysis is conducted using a descriptive approach to provide an overview of the research object and test hypotheses. The results of the research indicate that: 1. The method used to determine the qibla direction of Masjid Al-Mujahidin in Parepare is a combination of a compass and observations of the sun's shadow. 2. Calibration of the mosque's qibla direction reveals a deviation of one and a half degrees. Although this deviation is considered small, it can still be tolerated in certain circumstances or within certain parameters.